Diversidade e Distribuição Espacial de Fungos Fitopatogenicos Associados à Digitaria insularis e seu Potencial como Agentes de Controle Biológico - Garcia, Fernando (2024)
Sourgrass (Digitaria insularis L. Fedde) is a highly detrimental weed in Brazilian agriculture due to its competitive capacity with crops, fast growth, and aggressive spread, presenting biotypes resistant to chemical herbicides. Biological control emerges as a promising alternative. For sourgrass, necrotrophic and biotrophic phytopathogenic fungi stand out as potential biological control agents. This study aimed to present the spatial distribution of necrotrophic phytopathogenic fungi associated with sourgrass collected in the states of Minas Gerais, Goias, and São Paulo, and to estimate their occurrence in the collection areas. Additionally, it aimed to select necrotrophic fungi collected as potential biological control agents for D. insularis. Another objective was to compile and complement information on the potential of the fungus Anthracocystis panici-leucophaei as a biological control agent for D. insularis. Samples of D. insularis were collected from different locations in these states, and 204 necrotrophic fungal isolates were obtained and tested for pathogenicity. The study reveals the diversity and geographical distribution of phytopathogenic fungi associated with bittergrass, providing a basis for future research aiming at effective control of this weed. Among the tested isolates, 79 were considered pathogenic to sourgrass. Morphological and phylogenetic analyses allowed the identification of 67 of these isolates belonging to 17 fungal genera. Isolates KDI 0103, KDI 0145, KDI 0104, KDI 0164, KDI 0147 showed positive results both in seed germination inhibition and in aerial and radicle development control (in vitro). In vivo, isolates KDI 0204, KDI 0203, KDI 0042 showed positive results in both pre- and post-emergence, indicating consistent control potential at different phenological stages. A new species of Cladosporium was reported for the first time associated with Digitaria insularis. New information supports the potential of Anthracocystis panici-leucophaei, the causal agent of smut in D. insularis, as a biocontrol agent for sourgrass.